2020
DOI: 10.1021/acsami.0c02726
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity of Fullerene Derivatives Induced by Host–Guest Assembly

Abstract: Fullerenes have been recognized as good candidates for solid lubricants. In this study, the microscale superlubricity of fullerene derivatives was accomplished by the construction of regular host–guest assembly structures. Herein, the host–guest assembly structures of fullerene derivatives were successfully constructed on a highly oriented pyrolytic graphite (HOPG) surface by introducing the macrocycles as the templates and were explicitly revealed by scanning tunneling microscopy (STM). Meanwhile, the nanotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…coefficient is positively correlated with the absolute value of total energy per unit area. In other words, there is a positive correlation between friction coefficient and interaction strength, which agrees well with the conclusion in our previous researches (Shi et al, 2018;Tan S. C. et al, 2020). The interaction herein includes the interaction between assembled molecules and the interaction between molecules and HOPG substrate.…”
Section: Nanotribological Properties Of Liquid Crystalssupporting
confidence: 92%
See 1 more Smart Citation
“…coefficient is positively correlated with the absolute value of total energy per unit area. In other words, there is a positive correlation between friction coefficient and interaction strength, which agrees well with the conclusion in our previous researches (Shi et al, 2018;Tan S. C. et al, 2020). The interaction herein includes the interaction between assembled molecules and the interaction between molecules and HOPG substrate.…”
Section: Nanotribological Properties Of Liquid Crystalssupporting
confidence: 92%
“…Based on the theoretical calculation, it was concluded that the friction coefficients at nanoscale were positively correlated with the interaction strength in supramolecular assembly. And in our research of fullerene derivatives (Tan S. C. et al, 2020), we achieved the microscale superlubricity by the construction of ordered host-guest assembly structures. However, further investigation remains necessary to explore the mechanism of tribology and promote the achievement of superlubricity.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2, the most currently used carbon-based lubricant additives including fullerenes [74], graphene [75], nanographites [76], carbon nanotubes [77], and onion-like carbon [78]. Although the above carbonbased nanomaterials as additives exhibited favorable friction-reducing, anti-wear, and extreme pressure properties, they also have some fatal drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…As an additive in fluid lubrication, graphene can be added to different types of fluid lubrication systems to conspicuously improve the lubrication performance and is an ideal lubricant material for rotating/sliding contact. [ 18,19 ] The 3D graphene [ 20 ] we used is a new method to prepared 3D framework carbon (3DFC). Its comprehensive advantage is directly calcined sodium citrate without adding any additional carbon source, template and catalyst.…”
Section: Introductionmentioning
confidence: 99%